The System of Judicial Mediation in the Algerian Law of Civil and Administrative Procedure - MERAMRIA, Hamma (Journal of Human Sciences, 2019)
The system of judicial mediation as an alternative way to solve the conflicts through the optional, secret and fast procedures based on the trial to make the point of views of the parties in conflict convergent, which will be done through a third party called “the judicial mediator” who is in charge of the management of negotiation until achieving an accepted compromise between the parties.Regarding the advantages and characteristics of this system, the Algerian legislator begins with the establishment of this system within the law of civil and administrative law, and considers this system a compulsory procedure exposed by the judge to the parties in conflict. In this study, we treat the dispositions of the mediation focusing on its characteristics and the procedures of its implementation, in addition to the legal status of the judicial mediator.